Liver function differences in atherosclerotic cardiovascular disease: a multi-ethnic dual-cohort retrospective study - Wang, Yifei; Zhang, Zichen; Ren, Wenbo; Shi, Lin; Zhai, Taiyu; Huang, Jing (Frontiers in Endocrinology, 2025)
Background and aimsLiver function plays a pivotal role in the initiation and progression of atherosclerotic cardiovascular disease (ASCVD). Exploring the potential associations between liver function assessment indicators and ASCVD is essential for understanding the liver’s involvement in ASCVD pathogenesis. However, the specific relationships between these indicators and ASCVD are still debated. This study aims to conduct an in-depth comparative analysis of variations in various liver function assessment indicators among populations of ASCVD patients.MethodsA dual-cohort retrospective cross-sectional study design was employed, using data from 15,943 ASCVD patients at the First Hospital of Jilin University and 472 ASCVD patients from the National Health and Nutrition Examination Survey (NHANES) database. Liver function indicators, including enzymatic, protein synthesis, bilirubin metabolism indices, and lipid profile parameters, were analyzed. Inclusion and exclusion criteria were rigorously applied, followed by univariate regression, multivariate regression and stratified subgroup analyses.ResultsHepatocyte damage indicators (aspartate aminotransferase, alanine aminotransferase, gamma-glutamyl transferase, alkaline phosphatase) and total bilirubin were identified as risk factors for ASCVD. Albumin showed a protective effect. Globulin levels differed significantly between cohorts. Cholinesterase (cohort 1) and total protein, total cholesterol (cohort 2) showed no significant changes in ASCVD patients.ConclusionMany liver function indicators are correlated with ASCVD. There are differences in these indicators between ASCVD patients and healthy volunteers. Although some indicators may be weakly correlated due to confounding factors, this study still provides a scientific rationale for developing more precise ASCVD prevention and treatment strategies in the future.